2019
DOI: 10.1002/nafm.10267
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Fishery Gear Type and Handling Practices on Capture and Release of Wild Steelhead on the Bulkley River

Abstract: Steelhead Oncorhynchus mykiss are captured and released during spawning migrations by the commercial, subsistence (Indigenous), and recreational fishing sectors, though the consequences of these fisheries interactions on steelhead migration are poorly understood. This study evaluated injury, reflex impairment, behavior, and survival of released wild adult steelhead following capture in the subsistence dip-net, subsistence beach-seine, and recreational angling fisheries of the Bulkley River, British Columbia. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…Steelhead anglers almost exclusively target slow moving water or refuge sites where steelhead are known to hold prior to overwintering in the river (Keefer et al, 2009). These sampling groups therefore reflect fish in two different stages of migration and freshwater acclimation, which has been previously confirmed by telemetry (Twardek et al, 2019).…”
Section: Methodssupporting
confidence: 67%
See 4 more Smart Citations
“…Steelhead anglers almost exclusively target slow moving water or refuge sites where steelhead are known to hold prior to overwintering in the river (Keefer et al, 2009). These sampling groups therefore reflect fish in two different stages of migration and freshwater acclimation, which has been previously confirmed by telemetry (Twardek et al, 2019).…”
Section: Methodssupporting
confidence: 67%
“…This study found one mortality (1.5% of fish) that could not be readily explained by the capture event itself, which indicates that infectious agent-induced mortality is minimal for fish upstream of the falls (Twardek et al, 2018). The notion of migratory culling is partly supported by the described telemetry work (Twardek et al, 2018, 2019), but future telemetry studies should additionally include gill agent-transcriptome analyses such as performed herein.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations